Update from Canadian Respirology Program Directors (Canadian Respiratory Journal)
Submitted by Elizabeth Tullis MD FRCPC Associate Professor of Medicine, Respirology Program Director, University of Toronto, Toronto, Ontario The Canadian Organization of Pulmonary Program Directors (COPPD) had their first meeting in Montreal on November 7, 2003, which was sponsored by an unrestricted educational grant from AstraZeneca Canada Inc. This meeting was held in conjunction with the Royal College of Physicians and Surgeons (RCPS) Respirology Subspecialty Committee meeting held on November 6, 2003, and with the first Canadian Division Directors meeting held on November 8, 2003.